ANALGESIC AND PHYSIOLOGIC EFFECTS OF ELECTROACUPUNCTURE AND MEDETOMIDINE IN DOMESTIC GOATS - Z. Shah; T. Shah; I. Ahmad; S. Ahmad; S. B. Khan; T. Hussain; Abdullah; M. Sohail Nazif (Journal of Animal and Plant Sciences, 2023)
To evaluate the analgesic and physiological effects of electroacupuncture (EA) and medetomindine in domestic goats. Thirty healthy goats (aged 1-2 years and body weight 22±3.17 kg) were divided into five groups (6 goats/group). Group 1 animals were considered as a control; groups 2 and 3 animals were given 5μg kg-1 and 20μg kg-1 medetomidine IM respectively; group 4 animals were stimulated with EA for 30 mins and group 5 animals were given EA in combination with 5μg kg-1 medetomidine IM. The pain threshold in groups 2 and 3 animals were increased significantly (p < 0.05) at 15 to 60 mins compared to group 1. Group 5 animals showed an increase (p < 0.05) in pain threshold at 15 to 60 mins compared to animals in group 2 and group 4. Goats in groups 2 and 3 showed decrease (p < 0.05) in heart rate, respiratory rate, mean arterial pressure and rectal temperature, whereas animals in group 5 showed less effect on these physiological parameters. Furthermore, goats in group 5 did not any effect on blood cell count, serum chemistry, or liver health status. The combination of EA plus 5 µg kg-1 medetomidine produced adequate antinociception with minimal physiological alteration suggesting that, an effective strategy for clinical observation and minor surgical procedures in goat.
Keywords: Analgesic; electroacupuncture; goats; medetomidine; physiologic effect